L-selectin deficiency decreases aortic B1a and Breg subsets and promotes atherosclerosis - Gjurich, Breanne N.; Taghavie-Moghadam, Parésa L.; Ley, Klaus; Galkina, Elena V. (Thrombosis and Haemostasis, 2014)
There is a significant recruitment of leucocytes into aortas during atherogenesis. L-selectin regulates leucocyte migration into secondary lymphoid and peripheral tissues and was proposed to play a role in leucocyte homing into aortas. Here, we determine the role of L-selectin in atherosclerosis. L-selectin-deficient Apoe-/- (Sell-/-Apoe-/-) mice had a 74% increase in plaque burden compared to Apoe-/- mice fed a chow diet for 50 weeks. Elevated atherosclerosis was accompanied by increased aortic leucocyte content, but a 50% reduction in aortic B cells despite elevated B cell counts in the blood. Follicular B cells represented 65%, whereas B1a and regulatory B cells (Breg) comprised 5% of aortic B cells. B1a and Breg cell subsets were reduced in Sell-/-Apoe-/- aortas with accompanied two-fold decrease in aortic T15 antibody and 1.2-fold decrease of interleukin-10 (IL-10) levels. L-selectin was required for B1 cell homing to the atherosclerotic aorta, as demonstrated by a 1.5-fold decrease in the migration of Sell-/-Apoe-/- vs Apoe-/- cells. Notably, we found a 1.6-fold increase in CD68hi macrophages in Sell-/-Apoe-/- compared to Apoe-/- aortas, despite comparable blood monocyte numbers and L-selectin-dependent aortic homing. L-selectin had no effect on neutrophil migration into aorta, but led to elevated blood neutrophil numbers, suggesting a potential involvement of neutrophils in atherogenesis of Sell-/-Apoe-/- mice. Thus, L-selectin deficiency increases peripheral blood neutrophil and lymphocyte numbers, decreases aortic B1a and Breg populations, T15 antibody and IL-10 levels, and increases aortic macrophage content of Sell-/-Apoe-/- mice. Altogether, these data provide evidence for an overall atheroprotective role of L-selectin.
Keywords: Atherosclerosis; L-selectin; B cell subsets